2019
DOI: 10.3889/oamjms.2019.576
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Disease and Lower Extremities Artery Disease in Patients with Chronic Obstructive Pulmonary Disease

Abstract: AIM: To assess the frequency of carotid artery disease (CAD) and lower extremities artery disease (LEAD) in patients with chronic obstructive pulmonary disease (COPD) and their relation to the severity of airflow limitation and the level of C-reactive protein (CRP). METHODS: We performed a cross-sectional study including 60 patients with COPD (52 male, 8 female), aged 40 to 80 years, initially diagnosed according to the actual criteria. Also, 30 subjects in whom COPD was excluded, matched to COPD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The patients with non-SDB included 6 women and 5 men while the SDB group consisted of 12 men and 2 women. Although not statistically significant, the prevalence of women with plaques in the SDB group was lower than in men as previously described ( 30 , 31 ).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The patients with non-SDB included 6 women and 5 men while the SDB group consisted of 12 men and 2 women. Although not statistically significant, the prevalence of women with plaques in the SDB group was lower than in men as previously described ( 30 , 31 ).…”
Section: Resultssupporting
confidence: 73%
“…Additionally, the association between carotid plaques and COPD was previously documented. Bukliosaka-Ilievska et al ( 30 ) reported that 65% of patients with COPD had carotid plaques, and in a meta-analysis conducted by Ambrosino et al, COPD was significantly associated with subclinical atherosclerosis, particularly with a significantly thicker carotid IMT. Moreover, the prevalence of plaques was two times as high as compared with non-COPD controls, making COPD by itself a risk factor for the development of carotid plaques ( 31 ), likely due to the sustained hypoxia they experience.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency and severity of echocardiographic changes registered by 2D Doppler echocardiography in initially diagnosed COPD patients and non-COPD controls were compared in cross-sectional analysis. The study was conducted at the General Hospital "8th September", Skopje, in the period January -May 2018 as a continuum of our investigation of the impact of cardiovascular comorbidities on COPD (19). The study was approved by the Ethics Committee of the Medical Faculty at University "Sts.Cyril and Methodius", Skopje (03-2237/5/21.05.2018) [19].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The study was conducted at the General Hospital "8th September", Skopje, in the period January -May 2018 as a continuum of our investigation of the impact of cardiovascular comorbidities on COPD (19). The study was approved by the Ethics Committee of the Medical Faculty at University "Sts.Cyril and Methodius", Skopje (03-2237/5/21.05.2018) [19].…”
Section: Study Design and Settingmentioning
confidence: 99%
See 1 more Smart Citation